INTENTION AND BEHAVIOR OF TAX PAYMENT COMPLIANCE BY THE INDIVIDUAL TAX PAYERS LISTED IN PRATAMA TAX OFFICE WEST SIDOARJO REGENCY - Kautsar Riza Salman; Bayu Sarjono (Journal of Economics, Business, and Accountancy Ventura, 2013)
This study provides empirical evidence related to the effect of some factors such as compliancebehavior intention, and tax compliance behavior. These also include the attitude towards compliance,subjective norm, perceived behavioral control and the complexity of tax laws on the compliancebehavior intention. It also analyzes the effect of compliance behavior intention and complexityof tax laws on tax compliance behavior. This study uses individual taxpayers registered inTax Offices (KPP) in West Sidoarjo residence, who had filled out the Tax Filling Notification(SPT). The questionnaires were distributed to the individual tax payers with the total number of87 respondents. The data were analyzed using Partial Least Square (PLS). It was found that (1)subjective norms and perceived behavioral control are important components in influencing theintention to behave compliantly (Compliance behavior intention), (2) the complexity of the taxlaws is also an important component in influencing intention and behavior for compliance by thetaxpayers. This study cannot provide empirical evidence on the effect of attitude on Compliancebehavior Intention and the effect of compliance behavior intention on tax payers’ compliance.